Analysis of the mean electrical axis of the ventricular depolarization from standard electrographic leads in normal adult males - Prajapati, Rajesh; Amatya, Neebha; Magara, Rajab Rana; Shrestha, Ripti; Baral, Prakash; Mahotra, Narayan B (Journal of Karnali Academy of Health Sciences, 2024)
Background: The ECG is vital in diagnosing cardiovascular health by examining heart activity. This study investigates the relationship between the cardiac vector and body composition parameters (height, weight, BMI) in young Nepali males, aiming to improve ECG interpretation by identifying populationspecific physiological influences on cardiac vector orientation. The objective of this study is to analyze the correlation between the cardiac vector and physical attributes—height, weight, BSA, and BMI—in healthy males aged 18-25, establishing a reference for how these factors impact cardiac vector, thus enhancing ECG interpretation accuracy for this demographic.Methods: A cross-sectional study was conducted among 116 male subjects, aged 18-25 years, comprising students and staff of Gandaki Medical College Teaching Hospital and Research Center, Pokhara, Nepal, over the period from June to September 2023. Electrocardiograms (ECGs) were recorded using a standard ECG machine with conventional limb leads. The mean electrical axis of the heart for each individual was determined by plotting the net voltage of the QRS complex in Lead-I and Lead-III. The study aimed to analyze the correlation between the cardiac vector and physical measurements, such as height, weight, Body Surface Area (BSA), and Body Mass Index (BMI). Data analysis was performed using SPSS version 27.0.Results: The normal mean electrical axis of the healthy male subjects was observed as 57.88 24.55°. There was significant positive correlation of cardiac vector with height (p< 0.05), whereas negative correlation was observed with weight and BMI (p< 0.01). However, there was no significant correlation with BSA. In our study we observed the maximum left axis cardiac vector as -10° and right axis as 90° among 116 male subjects.Conclusion: We established a cardiac vector with values differing from those reported in other studies, using standard bipolar limb leads in normal, healthy male subjects. It is also examined that greater BMI has shifted the electrical activity of the ventricles to the left.